Pengembangan Kawasan Minapolitan (Studi Kasus : Pelabuhan Perikanan Samudera Cilacap) - Pancawati, Yuliarti Dian (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Cilacap district has the fishery potential of 72,000 tonnes per year, but only about 21% utilization. Ocean Fishing Port Cilacap Determination by the Ministry of Maritime Affairs and Fisheries as one of the pilot minapolitan-based fisheries led to the development of strategic Minapolitan to be implemented and is expected to provide a multiplier effect in the development of the region in Cilacap and improve the well-being of communities around the minapolitan region.Â This research was conducted with the aim to formulate the direction of development Minapolitan Ocean Fishing Port Cilacap. The technique of collecting data using interviews, documentation and observation. The sampling technique used is purposive sampling and snowball sampling. The analysis method used in this research is descriptive method qualitative and SWOT analysis.Â Based on the analysis and calculation of the external and internal factors Minapolitan Ocean Fishing Port Cilacap, the value of internal strengths and weaknesses by 2.2 by 0.9, so that the difference of the rersebut factor is 1.3. External factors obtained by the probability of 2.4 and 1.0 so that the difference between the value of the threat of these two factors is equal to 1.4. Ocean Fishery Port Minapolitan Cilacap have external internal position at the point (1,3; 1,4), namely in quadrant I. In other words, Minapolitan has strengths and opportunities that can be used to support aggressive growth policy (growth oriented strategy). SWOT analysis of the development Minapolitan Ocean Fishing Port Cilacap generating leads recommendation subsystem upstream, downstream subsystem, and subsystem support. As to realize it takes a strong commitment and coordination involving the relevant stakeholders.Â